Endurance und agility profile between male soccer players of different age categories - Shalaj, I.; Tishukaj, F.; Gjaka, M.; Ademi, B.; Pllana, A.; Wessner, B.; Csapo, R.; Tschan, H. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Elite performance in soccer depends upon a vast number of factors most important technical and tactical skills. However, evidence exists demonstrating that improved oxygen uptake enhances soccer performance and that modern soccer is characterized by an increasing number of brief, intensive actions such agility tasks. Aim The study aimed to assess differences in endurance- and agility performance between elite male soccer players of different age groups (U13, U15, U17) and compare them with senior elite players in Kosovo. Methods: 192 subjects (U13, n=59); (U15, n=48); U17 (n= 32), and 53 senior players were tested for body composition, endurance capacity and agility performance (IAT), respectively. A Multistage Fitness Test (20m shuttle test to exhaustion) was performed to assess aerobic capacity of the players, whereas Illinois Agility Test was used to determine agility performance. Analyses of variance (ANOVA) has been used to compare means in the different age groups. Results: As expected adult elite players had significantly better endurance and agility performance (p<0.001) compared to all other age groups. Surprisingly estimated VO2max of U13 players have been found to be significantly higher compared to players of U15 and U17 team, respectively (U13: 52.9±2.8; U15: 47.9±3.1; U17: 48.0±2.5 and adult elite players: 55.0±3.0). Conversely, using One-Way ANOVA showed that as chronological age increased, performance in agility increased significantly (p<0.001) among all categories. Weight and Illinois Agility Test were strongly and negatively correlated with aerobic endurance only among senior players (R2=0.50); (cc=-.475**). Discussion: Current study demonstrates that there is an age and developmentrelated development of agility and endurance performance with highest performance in adult elite athletes. Another finding is that excess weight has a negative impact on aerobic performance and IAT only in senior soccer players